Desenvolvimento de um programa de controle da qualidade para a tecnologia VMAT - Silva, Ricardo Goulart da (2013)
Modern radiation therapy keeps evolving and the technological changes include new imaging modalities, new patient immobilization devices and new treatment delivery systems. These advances have made it possible to reduce the dose to normal tissue structures and consequently minimize the risk of toxicity and morbidity, while allowing for dose escalation to the tumor volumes, potencially leading to improved locoregional control. Traditional IMRT techniques offer all of these features but the treatment session time is usually long, mainly for the head and neck cases. Currently, the VMAT technique is a reality in reference centers around the world. This technology has improved delivery efﬁciency over IMRT, decreasing the treatment application time, as this modality introduces extra degrees of freedom in the optimization process. The modulation of the radiation beams is achieved by simultaneous variation of dynamic parameters such as dose rate, gantry speed and leaves speed. The high level of complexity associated to the new treatment trends, inevitably, requires more accuracy and more rigorous quality assurance programs. The commissioning methods reported for the Varian RapidArc system were extended to an Elekta Synergy linear accelerator, using custom ﬁles built in the iComCAT software. Speciﬁc tests for the machine quality assurance are presented and also the dosimetric validation process applied to the Monaco treatment planning system. The MLC parameters, modeled by the Monte Carlo algorithm, were analyzed and the TG 119 tests were adapted for VMATplanning. In the end, a speciﬁc program developed for the VMAT technology for Elekta accelerators is presented.